Vitamin D Deficiency - Fedotova, Julia (IntechOpen, 2020)
Vitamin D is the topic for many discussions in the scientific community. Nowadays, a different interpretation of this secosteroid hormone is needed. Today the term "vitamin" may be considered outdated. This compound may be correctly be called a vitamin only when it is administered to humans or animals that suffer from its deficiency. This book attempts to clarify the role of Vitamin D deficiency in many pathological processes in the whole organism. Chapters in this book cover such issues as the earliest clinical and preclinical investigations of the consequences of Vitamin D deficiency for cognitive, cardiovascular, metabolic, immune, and renal disorders.